2016
DOI: 10.1002/srin.201500423
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Grain Oriented Silicon Steels Manufactured by Continuous Annealing

Abstract: Low-cost grain oriented silicon steel produced by continuous annealing, low slab-heating temperature, and omitting normalization annealing is explored and analyzed. This type of grain oriented steel is designed to replace the non-oriented steels used for the production of transformers of medium and small sizes as specified in all GO steel producers catalogs. Fully secondarily recrystallized structure with magnetic properties of P1.7 ¼ 2.04 W kg À1 and B8 ¼ 1.76 T is obtained at temperature of 1050 8C within 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Continuous annealing integrates cleaning, annealing, levelling and finishing, and has the advantages of a short production cycle, high yield, product diversification and high-quality products, improved properties and shape (Nishchik et al, 2016;Hou et al, 2018;Jiao et al, 2016). As an important process in the production of high-grade cold-rolled strip, continuous annealing provides raw material for subsequent levelling, so strip shape precision is important to the shape of finished product (Ma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Continuous annealing integrates cleaning, annealing, levelling and finishing, and has the advantages of a short production cycle, high yield, product diversification and high-quality products, improved properties and shape (Nishchik et al, 2016;Hou et al, 2018;Jiao et al, 2016). As an important process in the production of high-grade cold-rolled strip, continuous annealing provides raw material for subsequent levelling, so strip shape precision is important to the shape of finished product (Ma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the kinetic of secondary recrystallization was significantly accelerated by strain induced boundary migration mechanism. Recently, Jiao [16] reported a low-cost grain-oriented silicon steel manufacturing method by using a reduced inhibition state and two-stage cold rolling, and the secondary recrystallization was complete in continuous annealing. Furthermore, Lu [17] observed that some non-Goss {110} <227> grains abnormally grew during short-term isothermal secondary annealing in strip-cast Fe-4.5%Si grain-oriented silicon steel, and deemed that this non-Goss abnormal growth would lead to the decrease of magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Cleaning, annealing, leveling and finishing can be merged because of the continuous annealing process line (CAPL) that uses rapid heating, high-temperature annealing, rapid cooling and overaging treatment technologies (Jiang et al, 2016). A product with good flatness, uniform performance, and the surface of high cleanliness can be produced at a lower cost (Jiao et al, 2016). Thus, this CAPL has rapidly developed (Zheng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%